Governance and the mangrove commons: Advancing the cross-scale, nested framework for the global conservation and wise use of mangroves. (15th June 2022) - Walker, Julie E.; Ankersen, Thomas; Barchiesi, Stefano; Meyer, Courtney K.; Altieri, Andrew H.; Osborne, Todd Z.; Angelini, Christine
Abstract: Mangroves provide critical ecosystems services, contributing an estimated 42 billion US dollars to global fisheries, storing 25.5 million tons of carbon per year, and providing flood protection to over 15 million people annually. Yet, they are increasingly threatened by factors ranging from local resource exploitation to global climate change, with an estimated 35% of mangrove forests lost in the past two decades. These threats are difficult to manage due to the intrinsic characteristics of mangrove systems and their provisioning services, and their transboundary and pan-global nature. Due to their unique intertidal ecological niche, mangroves are often treated as a "common pool resource" within national legal frameworks, making them particularly susceptible to exploitation. Moreover, they form ecological connections through numerous biotic and abiotic processes that cross political boundaries. Because of these qualities a cross-scale nested framework of international, regional, and local coordination is necessary to successfully sustain mangrove ecosystems and their valuable services. Although coordination across the geopolitical spectrum is often cited as a need for effective management of common resources such as mangroves, there has been no formal analysis of mangrove multiscale governance. In this paper we address this gap by providing a comprehensive analysis of interactions between and within international, regional, and local mangrove management regimes and examine the challenges and opportunities such multiscale governance frameworks present. We highlight Costa Rica as a case study to demonstrate the universal relevance and potential of multi-scale governance and explore its downscale potential. Using Elinor Ostrom's principles for self-governance of the commons as our touchstone, we identify where improvements to the status quo could be implemented to increase its effectiveness of the current frameworks to meet the ongoing challenge of managing mangrove-derived resources and services in the face of a changing climate and human needs. Highlights: Mangroves cover 75% of tropical coastlines and provide numerous ecosystem services. Importance of mangroves is widely studied, yet they are being lost at an alarming rate. Vast extent of mangroves and their connections necessitate multiscale management. This novel analysis assesses management within and across multiple spatial scales. Identifying connections is needed to guide a multi-scale governance framework.